Health considerations for the year 2000 - J F Connor (Kansas Agricultural Experiment Station Research Reports, 1991)
As the swine industry matures, profit margins will decrease. Control of the major factors affecting feed cost will drive the system. Upgrading or maintaining health will be a major emphasis, because disease agents and complexes affect growing-finishing performance. Many diseases, such as pneumonia caused by Actinobacillus (llaemophilus) pleuropneumonia and swine dysentery, dramatically affect growing-finishing performance. Diseases decrease average daily feed intake (ADFI) and increase feed per gain ratio (FIG) in many instances. At the same time, they increase input costs via treatments, vaccines, and feed additives. Historically, our control methods may have been successful on individual farms, but not across large populations. Because of the dynamics of disease complexes, it has been difficult to understand the disease agents and/or their interactions, let alone define a cost-effective method of control or elimination. However, several new techniques offer hope of optimizing the genetic capability of growing-finishing pigs with respect to average daily gain (ADG) and F/G. These control measures become more important as restrictions increase on therapeutic feed additives, injectables, and the producer's goal of providing a pork product untainted by residues of any kind. Likewise, in the future, available carcass-enhancing products, such as Ractopamine, may not allow simultaneous use of therapeutics, requiring production systems with pigs of high health status.; Swine Day, Manhattan, KS, November 21. 1991
Keywords: Swine day; 1991; Kansas Agricultural Experiment Station contribution; no. 92-193-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 641; Swine; Health considerations; Modified early weaning